Dinamika Pendidikan Islam Pada Masa Penjajahan Belanda dan Jepang - Aji, Wahyu; Rama, Bahaking; S, Syamsuddin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to examine the dynamics of Islamic education in the context of the Dutch and Japanese colonial periods. The type of research is qualitative in the form of literature research using data collection techniques from the books and journals. The results of this research are that Islamic education during the Dutch colonial period is described in a dichotomous state (distinction based on its organizers, namely non-governmental organizations or the Dutch government and discriminatory (different treatment between self-supporting educational institutions and colonial educational institutions). Meanwhile, Islamic education during the Japanese colonial period is described as a process bright because the Japanese government reactivated the madrasah which was closed by the Dutch government and gave it a lot of assistance and support in various forms for the progress of the madrasah and made it equal with public schools even though in the end it was read as just a "mask".